Probing Dynamic Mechanical Analysis and Atomic Force Microscopy of Polypropylene/Kaolin Nanocomposite - Zago, Dagaci Muhammad; Jika, Suzi Salwah Binti; Badarulzaman, Nur Azam Bin; Ruslan, Nurun Najwa Binti; Nuhu, Awwal Hussain; Bano, Nazia (International Journal of Engineering and Technology, 2018)
The Dynamic mechanical analysis (DMA) and Atomic force microscopy (AFM) studies were conducted and evaluated on polypropylene/kaolin (P/K) nanocomposite treated with maleic anhydride (MA) and dicumyl peroxide (DCP) as additives in an in- situ process.Â  Two-roll mill was used in compounding of the nanocomposites while moulding were done by injection moulding machine. Investigation in to the effect of K and MA/DCP on the nanocomposites (NCs) indicates that interfacial interactions between PP and K as filler was eminent. DMA analysis reveals an increase in the storage modulus which was at maximum significantly in P/K NC with 3 wt% and decrease in damping factor tan Î´ also at P/K NC of 3 wt%. The AFM study indicates that there was uniform and smooth surface roughness among the NCs. Thus, addition of MA/DCP on to P/K NC improves the reinforcing influence on the nanocomposites for better improvement.